109 Predictors of readmission after trauma: A retrospective cohort study in New Zealand. (20th November 2022) - Harcombe, Helen; Barson, Dave; Samaranayaka, Ari; Davie, Gabrielle; Wyeth, Emma; Derrett, Sarah
Abstract : Background: In New Zealand, approximately 2000 people are admitted to hospital with major trauma annually. Following discharge, some are readmitted to hospital for a range of causes. Understanding the reasons behind such readmissions is important, particularly to develop/expand interventions to prevent avoidable readmissions. Aims: To describe the incidence of, and sociodemographic, injury-related and treatment-related factors predictive of hospital readmission related to: a) all-causes, b) the index trauma injury, and c) subsequent injury events in the 30 days and 12 months following discharge for major trauma patients in New Zealand. Methods: Data from the New Zealand Trauma Registry (NZTR) was linked with hospital discharge data from the Ministry of Health. Hospital readmissions were examined for all patients entered into the NZTR for an injury event between 1 January and 31 December 2018. Results: Of the cohort of 1986 people, 42% had at least one hospital readmission in the 12 months following discharge; 15% were readmitted within 30 days of discharge. Factors predictive of all-cause readmissions within 12 months included: being older, having comorbidities, the place and mechanism of the trauma injury, being admitted to an intensive care unit and length of hospital stay. Conclusion: Almost half of those admitted to hospital with major trauma are readmitted within 12 months of discharge with a range of factors associated with readmission. Learning Outcomes: Factors identified in this study will be useful in considering interventions for targeted strategies to prevent future readmissions.